Halftoning band gap of InAs/InP quantum dots using inductively coupled argon plasma-enhanced intermixing - Xu, C. D. (2010)
Inductively coupled argon plasma-enhanced intermixing of InAs/InP quantum dots grown on InP substrate is investigated. Intermixing is promoted by the near-surface defects generated by plasma exposure in annealing at a temperature of 600  degrees celcius for 30 s. The annealing results in a maximum differential band-gap blueshift of 106 nm but a thermal shift of only 10 nm. Band-gap halftones are obtained by controlling the amount of near-surface defects via wet chemical etching on the plasma-exposed InP cap layer. No degradation of quantum-dot crystal quality due to the process has been observed as evidenced by photoluminescence intensity.